Literature Review: Analisis Instagram Sebagai Media Pemasaran - Hardiansyah, Fikri (Jurnal Pelita Teknologi, 2023)
In the ever-growing digital era, social media has become an integral part of business marketing strategies. Instagram, as one of the leading social media platforms, offers great opportunities for companies to promote their products and services. This research aims to analyze the role of Instagram as a marketing tool and to evaluate its effectiveness in achieving marketing goals. The method in this research uses System Literature Review (SLR). The results of this research reveal that Instagram can be a very effective marketing tool, especially in creating high interaction and engagement with the audience.